Analisis Pengaruh Game E-Sport terhadap Aspek Kognitif Peserta Didik di SMAN 7 Balikpapan - Sani, Fadhlur; Iwandana, Dody Tri (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2024)
The students in SMAN 7 Balikpapan were the subjects of this research. The research method employed was quantitative, with a sample consisting of members of the e-sports extracurricular activity at SMA 7 Balikpapan, known as "SMAVEN ERA," totaling 45 individuals. Data collection for this study utilized a questionnaire as the instrument, which was subsequently processed using the IBM SPSS Statistics 26 software. The research findings revealed that out of the 45 students, 35 (77.78%) played e-sports at a moderate level, while 10 (22.22%) played e-sports at a high level. Regarding the cognitive aspect, it was determined that out of the 45 students, 6 (13.3%) exhibited a highly proficient cognitive aspect, 29 (64.4%) had a good cognitive aspect, and 10 (22.2%) had a reasonably good cognitive aspect. Further analysis through partial calculations yielded a t-value of 0.773, indicating that e-sports did not have a positive and significant influence on the students' cognitive abilities. Additionally, the correlation coefficient between the e-sports variable and cognitive ability showed a value of 0.044, with a determination coefficient of 0.002. This suggests that e-sports had a 0.02% influence on the cognitive aspect, while the remaining 99.08% was influenced by other unexamined variables. Therefore, it can be concluded that although e-sports are popular among students, they do not have a significant impact on the students' cognitive aspects. It is important for teachers and parents to provide a proper understanding of responsible usage of e-sports and to prioritize Physical Education, Health, and Sports (PJOK) in efforts to improve the overall health and cognitive development of the students. Keywords: E-sports, Cognitive, Physical Education, Health, and Sports (PJOK).